Pengembangan Desa Wisata melalui Pelatihan dan Pembinaan - Satria Bangsawan; Mahrinasari MS; Ayi Ahadiat; Ribhan Ribhan; Fajrin Satria Dwi Kesumah; Angga Febrian (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: The objectives of Tourism Village development in “Pulau Legundi”, Pesawaran District, Lampung Province is to know the societies’ motivation in developing entrepreneurship based on tourism village service, the ability of society in understanding how to develop tourism village, and the readiness of society to engage in tourism village development in order to improve their prosperity. Method: The three-step method used is that the first is preparation to identify the potential resources and the societies’ readiness to accept the community service in terms of Tourism Village development, the second is to conduct training and coaching, and then followed by monitoring and evaluation. Results: The results show that the knowledge, spirit and motivation, and understanding insights in developing Tourism Village increase after getting the training and coaching programs. Conclusions: Tourism Village in “Pulau Legundi” Village is very important to be developed to increase the prosperity of the society by creating the tourism attractions, providing information technology infrastructure and strengthening the motivation of the village governor by relevant government role, continuing training and coaching programs to improve the competence of the Tourism Village entrepreneurs, and implementing marketing communication through marketing digital content that is disseminated in the internet and social media.